Cholinesterase as a target for drug development in alzheimer’s disease - Sharma P.; Tripathi M.K.; Shrivastava S.K. (My University, 2025)
Alzheimer’s disease (AD) is an enormous healthcare challenge, and 50 million people are currently suffering from it. There are several pathophysiological mechanisms involved, but cholinesterase inhibitors remained the major target from the last 2–3 decades. Among four available therapeutics (donepezil, rivastigmine, galantamine, and memantine), three of them are cholinesterase inhibitors. Herein, we describe the role of acetylcholine sterase (AChE) and related hypothesis in AD along with the pharmacological and chemical aspects of the available cholinesterase inhibitors. This chapter discusses the development of several congeners and hybrids of available cholinesterase inhibitors along with their binding patterns in enzyme active sites. © Springer Science+Business Media, LLC 2020.